(untitled) (Web of Teachers: Inderscience Research, 2025)
Nitrogen, an element with a chemical sign N and an atomic number of 7, is one of the most abundant gases in nature. It is found primarily in the air, in the body of plants and animals, as well as in various mineral and organic compounds. The specific properties of nitrogen and its role in natural processes have made it an important element for scientific research and industry.